2012
DOI: 10.1016/j.oraloncology.2012.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tyrosine receptor kinases in the interactions of head and neck squamous cell carcinoma cells and fibroblasts

Abstract: Summary Despite treatment advancements, disease-free survival of head and neck squamous cell carcinoma (HNSCC) has not significantly improved. This may be a result of tumor-fibroblasts interactions providing protective pathways for oncogenic cells to resist therapy. Further understanding of these relationships in HNSCC may improve effectiveness of targeted therapies. In this article, we investigated the role of several receptor tyrosine kinases (RTK) in the interactions between HNSCC cells and supporting cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Oral cancer can also develop independent of this typical progression 30,31 . In either case, the development of OSCC is accompanied by changes in intercellular signaling between tumor cells and non-tumor cells, such as fibroblasts in the tumor microenvironment leading to dysregulation of gene expression and protein products facilitating cancer progression and metastasis 8,32,33 . Understanding of the molecular mechanisms underlying OSCC progression is essential to afford the opportunity to develop novel strategies to suppress tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Oral cancer can also develop independent of this typical progression 30,31 . In either case, the development of OSCC is accompanied by changes in intercellular signaling between tumor cells and non-tumor cells, such as fibroblasts in the tumor microenvironment leading to dysregulation of gene expression and protein products facilitating cancer progression and metastasis 8,32,33 . Understanding of the molecular mechanisms underlying OSCC progression is essential to afford the opportunity to develop novel strategies to suppress tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Because other receptors targeted by the drug are not expressed at appreciable levels, the effect is assumed to be mainly mediated through VEGFR and FGFR. Sweeny et al (11) demonstrated that dovitinib yielded significant cell count reductions in their HNSCC in vitro models. Konecny et al (37) demonstrated significant cell count reductions in endometrial cancer cell lines harboring activating FGFR2 mutations, and FGFR2 was also highly expressed in all of our cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Complex relationships exist between the oncogenic stroma and its surroundings in this heterogeneous disease (11). Cells from the immune system, the tumor vasculature and lymphatic systems and cancer associated fibroblasts (CAF) can encourage tumor growth, invasion and metastasis (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…PIP3 is converted back into PIP2 through the action of the lipid phosphatase PTEN, thus terminating the PI3K-initiated signal and avoiding further Akt activation [ 14 ]. Growth factor receptor over-expression [ 15 , 16 ], mutation and down-regulation of PTEN protein [ 17 ] and amplification of the PIK3CA gene (the gene coding for the catalytic unit of PI3K) [ 18 ] can lead to increased Akt activity. Enhanced Akt activity has indeed been found in 20 to 60% of tumor samples and in the majority of HNSCC-derived cell lines [ 18 21 ].…”
Section: Introductionmentioning
confidence: 99%